Membangun Kepercayaan Konsumen di Kota Kupang untuk Berbelanja secara Online Melalui E-Wom dan E-Service Quality - Alya Elita Sjioen; Jofret Umbu Soru Peku Djawang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Trust has a very important role in having an impact on consumer loyalty in the competitive environment of e-commerce. Lack of consumer trust can give a negative impression to the electronic word of mouth provided and electronic service quality. The population in this research is all Kupang City residents who have shopped online. The sampling technique used a purposive sampling method, namely a sample of 100 Kupang City residents who had shopped online. The data collection tool uses a questionnaire and the measurement scale uses a Likert scale. The data analysis technique uses structural equation modeling (SEM). The results of the research are that e-service quality has a significant and positive influence on the e-WOM of the people of Kupang City who shop online. E-service quality does not have a significant impact on consumer confidence in Kupang City who shop online. E-WOM has a significant impact on consumer confidence in Kupang City who shop online. Indirectly, e-service quality and e-WOM as intervening variables have a significant and positive impact on consumer confidence in Kupang City who shop online. The advice that can be given is for business people, especially MSMEs in the Kupang City Region, to utilize online media as an online shop to market their business products or services with good electronic service quality, then the electronic word of mouth of the people of Kupang City who shop online will be positive and if electronic word of mouth provides positive information, the level of consumer confidence in Kupang City who shop online is higher, which has an impact on sales turnover.